Human resource management and lecturers’ professional performance: The moderating role of continuing professional development: English - Wayan, Sri Maitri; Lasmi, Ni Wayan; Putra P, Komang Widhya Sedana (Journal of Profession Education, 2025)
This study examines the effect of Human Resource Management (HRM) practices on lecturers’ professional performance and investigates the moderating role of Continuing Professional Development (CPD) in this relationship. A quantitative research design was employed using a structured questionnaire distributed to lecturers at higher education institutions that have implemented formal HRM policies and CPD programs. The collected data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that effective HRM practices significantly enhance lecturers’ professional performance. In addition, Continuing Professional Development is found to strengthen the relationship between HRM practices and professional performance, suggesting that lecturers who actively engage in continuous learning are better able to translate HRM policies into improved professional outcomes. These results are consistent with Human Capital Theory and Social Exchange Theory, which emphasize the importance of sustained investment in employee development and organizational support. Practically, the study highlights that professional development initiatives are most effective when integrated with supportive and well-structured HRM systems. Higher education institutions are therefore encouraged to align CPD programs with strategic HRM practices to foster sustainable improvements in lecturers’ professionalism and performance.